إسهامات أساليب التحليل المالي الحديث في التنبؤ بالفشل المالي لمجمعات الشركات - عوني, محمد الصغير (Universty of Eloued جامعة الشهيد حمه لخضر, 2022)
الملخص: تهدف هذه الدراسة إلى التعرف على مدى إمكانية التنبؤ بالفشل المالي في المؤسسات الإقتصادية بإستعمال أساليب التحليل المالي الحديث، فالفشل المالي يعتبر من أهم المشاكل التي قد تواجه هذه المؤسسات. ولتحقيق أهداف الدراسة تم إسقاطها على مجمع صيدال، وذلك من خلال تحليل قوائمها المالية وإستخراج النسب المالية الأكثر دلالة، بالإضافة إلى تطبيق بعض نماذج للتنبؤ بالفشل المالي عليها في الفترة الممتدة من 2016 إلى 2020. وقد خلصت الدراسة إلى العديد من النتائج النظرية والتطبيقية أهمها أن الأساليب التقليدية للتحليل المالي تملك الأفضلية فيما يخص القدرة التحليلية لعملية التنبؤ بالفشل المالي مقارنة بالأساليب الحديثة، ويرجع سبب الاختلاف إلى النظرة التقليدية للمؤسسات الجزائرية للغاية من وجودها وغياب النظرة الجيدة، بالإضافة إلى عدم كفاءة السوق المالي في الجزائر وكذا محدودية المعلومات المالية بسبب التلاعب بالنتائج بما يتماشى مع الأهداف الشخصية للمسيرين والمحاسبين داخل المؤسسات. Résumé :فرنسية أو انجلزية This study aims to identify the extent to which financial failure in economic institutions can be predicted using modern financial analysis methods. Financial failure is one of the most important problems that these institutions may face. To achieve the objectives of the study, it was projected onto Saidal Complex, by analyzing its financial statements and extracting the most significant financial ratios, in addition to applying some models to predict financial failure on them in the period from 2016 to 2020. The study concluded with many theoretical and applied results, the most important of which is that the traditional methods of financial analysis have the advantage with regard to the analytical ability of the process of predicting financial failure compared to the modern methods, and this result is due to the difference due to the traditional view of the Algerian institutions very much from their presence and the absence of a good outlook, in addition to the inefficiency The financial market in Algeria, as well as the limited financial information due to the manipulation of results in line with the personal goals of managers and accountants within the institutions.
– دراسة عينة المجمع الصناعي صيدال (2016-2020)
أطروحة دكتوراه تخصص محاسبة مالية في العلوم الإقتصادية
Keywords: التحليل المالي، الفشل المالي، أساليب التحليل المالي الحديث، نماذج التنبؤ.; financial analysis, financial failure, Modern financial analysis methods, prediction models